The Role Of Organizational Commitment On Organizational Citizenship Behavior In Hotel Industry - Endo Wijaya Kartika; Chintya Pienata (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
There are many studies that focused on the role of organizational commitment on Organizational Citizenship Behavior (OCB) specifically conducted in Indonesia. However, few of studies emphasizeon the role of three conceptual constructsof organizational commitment namely affective, normative, and continuance on OCB in Indonesian context. Several empirical studies still remain inconclusive due to the inconsistency results. This research is intended as an empirical test to examine the role of three conceptual dimensions of commitment on OCB, and also tested to add body of knowledge about the results of this empirical study in Indonesia especially in hospitality industry. This is a quantitative causal research with 73 three-starred hotels’ employees as the respondents. The data is processed using SmartPLS 2.0 as the statistical tools, and as the result it is found that affective commitment affects positively and significantly toward OCB; normative commitment affects positively and significantly toward OCB; and lastly continuance commitment affects positively and significantly toward OCB.